Women's Empowerment Through Da'wah Bil Hal: Strategies Towards Sustainable Development in the Modern Era - Rochmah, Putri Indrawati; Nurhalizah, Mevy Eka (Nursyam Center, 2024)
This research aims to examine more deeply the role of da'wah bil hal in achieving the goal of women's empowerment towards sustainable development. Da'wah bil hal is da'wah accompanied by morals and concrete actions, one of which is through women's empowerment. Women's empowerment can be carried out from social, economic, inclusive education, and environmental aspects. Women's empowerment is in line with the fifth goal of the Sustainable Development Goals (SDGs), namely gender equality. The promotion of women working in the public sector is based on family economic interests, independence, understanding of socio-economic challenges, and improving social status. Through library research and case analysis methods, this research reveals the potential of da'wah bil hal in changing women's mindsets, increasing participation in sustainable development, and encouraging the creation of a fairer, more prosperous society without discrimination. Based on the data obtained by researchers, through women's empowerment, they can improve the quality of women's lives by applying da'wah bil hal which has the principles of equality and justice which is a solution to overcome problems and can be sustainable.